2015
DOI: 10.1371/journal.pone.0134094
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of the Dutch-Flemish PROMIS Pain Interference Item Bank in Patients with Chronic Pain

Abstract: The Dutch-Flemish PROMIS Group translated the adult PROMIS Pain Interference item bank into Dutch-Flemish. The aims of the current study were to calibrate the parameters of these items using an item response theory (IRT) model, to evaluate the cross-cultural validity of the Dutch-Flemish translations compared to the original English items, and to evaluate their reliability and construct validity. The 40 items in the bank were completed by 1085 Dutch chronic pain patients. Before calibrating the items, IRT mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 50 publications
3
37
1
1
Order By: Relevance
“…In addition, the study reported here and previous PROMIS ® Pain Interference analyses assume normality of the latent trait distribution. 25 Finally, the results of this study should be replicated in other samples before final conclusions can be reached about the validity of comparisons between Spanish and English speaking groups.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the study reported here and previous PROMIS ® Pain Interference analyses assume normality of the latent trait distribution. 25 Finally, the results of this study should be replicated in other samples before final conclusions can be reached about the validity of comparisons between Spanish and English speaking groups.…”
Section: Discussionmentioning
confidence: 89%
“…For the assessment of potential language DIF in PROMIS measures, to date researchers have used DIF analysis in an ordinal regression framework (Crane et al, 2006) and its implementation in the lordif-package (Choi, Gibbons, & Crane, 2011) with a criterion of R 2change of 0.02 (Crins et al, 2015;Hahn et al, 2014;Oude Voshaar et al, 2014;Paz et al, 2013). In case of absence of language DIF, parameters from the US calibration sample have been simply used in other languages as well (Hahn et al, 2014;Paz et al, 2013) For all items we unconstrained item parameters from the baseline model one at a time in the German sample.…”
Section: Dif Analysismentioning
confidence: 99%
“…Some PROMIS item banks have already been evaluated regarding language DIF, in particular Physical Functioning between US and Latino (Paz, Spritzer, Morales, & Hays, ) as well as US and Dutch samples (Oude Voshaar et al, ), Pain Interference between US and Dutch samples (Crins et al, ), and Social Health between US and Spanish‐speaking samples (Hahn et al, ). While a substantial impact of language related DIF was found in Physical Functioning between US and Latino (Paz et al, ), in others language‐related DIF was negligible (Crins et al, ; Oude Voshaar et al, ) or even absent (Hahn et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For pediatric populations, there are PROMIS-25, PROMIS-37, and PROMIS-49, each assessing anxiety, depressive symptoms, fatigue, pain intensity and interference, mobility and peer relationships. They can either be self-completed (ages [8][9][10][11][12][13][14][15][16][17] or completed by a parental proxy (ages [5][6][7][8][9][10][11][12][13][14][15][16][17]. Distinct from the Profiles, there is also a PROMIS global instrument which serves as a brief (10 item adult, 7/9 item pediatric) measure of physical and mental health.…”
Section: As Profile Instrumentsmentioning
confidence: 99%